Frequency domain analysis of guided resonances and polarization selectivity in photonic crystal membranes - Kupec, Jan; Akcakoca, Ugur; Witzigmann, Bernd (Journal of the Optical Society of America B-Optical Physics, 2011)
Microstructured photonic crystal membranes are of great interest as compact filters in a variety of fields, including telecommunication and sensing. Here we present an analysis of the transmission and resonance behavior of a dielectricmembrane featuringperiodically arrangedholesusing the frequencydomain finite element analysis.We solveboth the source aswell as eigenvalue problemfor a given geometry. Applying symmetry considerations,we discardmodes that cannot be excited by incident transverse electro-magnetic (TEM) light simultaneously.We relate the results of the source problemto the modal analysis and obtain strong correspondence in both frequency and resonance quality factor. We find that the sharp resonances can be related to the eigenmodes of a rectangular dielectric resonator formed by the membrane and the holes of the photonic crystal. Analyzing noncircular holes for polarization-dependent transmittivity, the modal analysis presented herein constitutes a powerful tool to understand and identify occurrence of pronounced wideband polarization selectivity. © 2010 Optical Society of America.
CRIS-Team Scopus Importer:2021-06-11